FRAMING INNOCENCE AND CONTROVERSY: A CRITICAL DISCOURSE ANALYSIS OF BALENCIAGA’S 2022 ADVERTISING CAMPAIGN EXPLOITING CHILDREN - Anak Bahasan , Aedelica Averil; Abdul Jabar, Nor Fatin (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
This study examines the 2022 Balenciaga holiday advertising campaign as a significant illustration of how luxury fashion intentionally utilizes controversy, child imagery, and sexualized aesthetics to garner attention and bolster cultural capital. The research utilizes Critical Discourse Analysis (CDA), grounded in Fairclough’s three-dimensional model and Kress and van Leeuwen’s visual grammar, to analyze a corpus comprising official campaign visuals, corporate statements, news reports, and social media comments. Textual research illustrates how multimodal configurations aestheticize references to bondage culture and judicial discourse while preserving a facade of juvenile innocence. An examination of discursive practices indicates that Balenciaga's framing strategies—particularly via vague apologies and blame-shifting language—function to diminish accountability. Social practice analysis situates the conflict within broad paradigms of neoliberal consumerism, shock marketing, and moral panic. Studies show that public outrage not only opposes the campaign but also unintentionally makes it more well-known, turning moral outrage into digital capital. The paper asserts that the Balenciaga incident illustrates the dynamics of power, representation, and accountability in modern advertising, where transgression functions as a profitable rhetorical tactic. This paper contributes to the discourse on child representation and corporate ethics in high-fashion branding by synthesizing Critical Discourse Analysis with visual semiotics, ultimately promoting the necessity for more stringent ethical review procedures and enhanced critical media literacy to empower audiences to identify and challenge detrimental ideological frameworks.